Chromium-free passivator as well as preparation method and application thereof
By using a chromium-free passivator containing metal salts, acrylic-phosphate copolymers, lactose, chelating agents and additives in the manufacture of lithium batteries, the problem of insufficient performance of existing chromium-free passivator in terms of corrosion resistance and long-term stability is solved, and the comprehensive performance of copper foil and the safety and service life of lithium batteries are improved.
Patent Information
- Application Number
- CN202510039888.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
The existing chromium-free passivating agents have problems such as poor results, complex processes, single ingredients and slow reaction speed in lithium batteries, making it difficult to achieve the protective effect of chromium-containing passivating agents, especially in terms of corrosion resistance and long-term stability.
A chromium-free passivator is used, and its formulation includes metal salts, acrylic-phosphate copolymers, lactose, chelating agents and additives. By optimizing the formulation design and process flow, the rapid film formation and comprehensive performance improvement of the passivator is achieved.
The chromium-free passivator not only abandons the toxic chromate components and avoids environmental pollution, but also significantly improves the corrosion resistance, heat resistance and oxidation resistance of copper foil, simplifies the process flow and reduces production costs, and extends the service life of lithium batteries.
Smart Images

Figure CN119876928A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of passivators, and in particular to a chromium-free passivator and a preparation method and application thereof. Background Art
[0002] In the manufacturing process of lithium-ion batteries, copper foil is used as the negative electrode current collector material, and its surface treatment is crucial to the overall performance of the battery. Traditionally, copper foil surface treatment relies on passivators containing chromates to form a protective film to enhance the corrosion resistance of copper foil and improve the binding force with active substances. However, chromates are toxic and known carcinogens, which not only pose a threat to human health, but also cause serious pollution to the environment. Therefore, the development of environmentally friendly and high-efficiency chromium-free passivators has become an important research direction in the industry.
[0003] Although some chromium-free passivators have appeared on the market, they generally have problems such as poor effect, complex process, single composition and slow reaction speed. Many chromium-free passivators are difficult to achieve the same protective effect as chromium-containing passivators, especially in terms of corrosion resistance and long-term stability. In addition, some alternatives require complex multi-step processing processes, which increases production costs and operational difficulties. At the same time, some chromium-free passivators rely only on a single ingredient or a simple combination, and cannot provide comprehensive performance improvements, such as improving corrosion resistance, heat resistance and oxidation resistance at the same time. Finally, some existing chromium-free passivators have a slow film-forming speed, which affects production efficiency. These problems limit the large-scale application and development of chromium-free passivators.
[0004] Therefore, there is an urgent need to develop a new chromium-free passivating agent that can simplify the process flow while comprehensively improving the physical and chemical properties of copper foil to ensure its excellent performance in lithium batteries. Summary of the invention
[0005] In view of this, the present invention proposes a chromium-free passivator and its preparation method and application. The passivator not only has good corrosion resistance and long-term stability, but also has rapid film-forming properties, which can comprehensively improve the heat resistance and oxidation resistance of copper foil, thereby promoting the further development of lithium battery technology.
[0006] In a first aspect, the present application provides a chromium-free passivation, which comprises the following components, calculated by weight: 1 to 15 parts of a metal salt; 0.2 to 0.5 parts of an acrylic acid-phosphate copolymer; 2 to 3 parts of lactose; 2 to 9 parts of a chelating agent and 3 to 11 parts of an auxiliary agent.
[0007] On the basis of the above technical solution, preferably, the metal salt, calculated by mass, includes: 0-5 parts of zirconium salt; 0-5 parts of titanium salt and 0-5 parts of molybdenum salt; the metal salt includes at least one of zirconium salt, titanium salt or molybdenum salt.
[0008] On the basis of the above technical scheme, preferably, the zirconium salt is selected from one of zirconium oxychloride, zirconium nitrate or zirconium sulfate; the titanium salt is selected from one of titanium sulfate, titanium nitrate or tetraisopropoxy titanium; the molybdenum salt is selected from one of ammonium molybdate, sodium molybdate or molybdenum trioxide.
[0009] On the basis of the above technical solution, preferably, the chelating agent is selected from at least one of ascorbic acid, gluconic acid or tetrasodium iminodisuccinate.
[0010] On the basis of the above technical solution, preferably, the auxiliary agent, calculated by weight, includes: 2 to 5 parts of accelerator and 1 to 6 parts of dispersant.
[0011] On the basis of the above technical solution, preferably, the promoter is phytic acid, and the dispersant is selected from 2-naphthalenesulfonic acid formaldehyde polymer sodium salt and / or sodium methylene bismethyl naphthalene sulfonate.
[0012] In a second aspect, the present invention relates to a method for preparing the above-mentioned chromium-free passivating agent, comprising the following steps:
[0013] S1, dissolving metal salts in deionized water respectively, adjusting the pH value, preparing corresponding salt solutions, and mixing; dissolving lactose, acrylic acid-phosphate copolymer, and chelating agent in water respectively to obtain corresponding solutions;
[0014] S2, adding the accelerator to part of the salt solution in step S1 under stirring, and mixing;
[0015] S3, sequentially adding the acrylic acid-phosphate copolymer solution, lactose solution, chelating agent solution and the mixed solution of step S2 to the remaining salt solution of step S1, stirring and mixing, adjusting the pH value of the solution, and finally adding a dispersant and stirring to obtain a chromium-free passivator for copper foil for lithium batteries.
[0016] Based on the above technical solution, preferably, in step S1, the concentration of the salt solution is 1-15 g / L, and the pH value is 3-6; the concentration of the lactose solution is 2-3 g / L; and the concentration of the acrylic acid-phosphate copolymer solution is 0.2-0.5 g / L.
[0017] On the basis of the above technical solution, preferably, in step S2, the mixing temperature is 30-40°C; the mass of the salt solution in step S2 is 30-50% of the mass of the salt solution in step S1.
[0018] On the basis of the above technical solution, preferably, in step S3, the pH value of the adjustment solution is 4 to 5.5.
[0019] On the basis of the above technical solution, preferably, in step S3, after adding the dispersant, stirring is performed for 10 to 30 minutes.
[0020] In a third aspect, the present invention relates to the use of the above-mentioned chromium-free passivator in copper foil for lithium batteries.
[0021] In summary, the present invention includes at least one of the following beneficial technical effects:
[0022] 2. The chromium-free passivating agent of the present invention abandons the toxic and harmful chromate components, thereby avoiding the pollution risk caused by the traditional chromium-containing passivating agent to the environment.
[0023] 3. The chromium-free passivator of the present invention can bond with copper ions by adding acrylic acid-phosphate copolymer, generate a strong cross-linking structure during the drying process, and further enhance the stability and adhesion of the passivation film; secondly, lactose can not only be used as a filler, but also has a certain antioxidant property due to the hydroxyl group in its molecular structure, which helps to protect other components from oxidation. When it works together with the chelating agent, it can further protect the stability of the metal salt in the copper foil used for lithium batteries; finally, by adding the promoter phytic acid, rapid passivation can be achieved to accelerate the film formation process.
[0024] 4. The chromium-free passivating agent of the present invention is suitable for various types of copper foil surface treatment and can effectively improve the safety and service life of lithium batteries.
[0025] 5. The method for preparing a chromium-free passivator of the present invention realizes the preparation of an environmentally friendly, efficient and high-performance copper foil chromium-free passivator for lithium batteries by optimizing the formula design and process flow. The method adopts the method of adding a metal salt solution step by step to ensure the uniform dispersion and effective reaction of each component, simplify the process steps and reduce the production cost. The final product exhibits excellent corrosion resistance, heat resistance, salt spray resistance and oxidation resistance, greatly improving the safety and service life of lithium batteries, and meeting the dual requirements of modern battery manufacturing for high efficiency and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The scanning electron microscope images of the copper foil before and after the treatment with the chromium-free passivation agent prepared in Example 1 of the present invention are provided; in the figure, (a) is the untreated copper foil; (b) is the copper foil treated with the chromium-free passivation agent in Example 1 of the present invention;
[0028] Figure 2 These are photos of copper foils immersed in antioxidant solutions under different conditions before and after being treated with the chromium-free passivator prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The materials mainly involved in the following examples are all conventional commercial products unless otherwise specified.
[0031] Table 1 Material source description
[0032] product factory Zirconium salt Aladdin Reagent Titanium salt Aladdin Reagent Molybdenum salts Aladdin Reagent ascorbic acid Shanghai MacLean Biochemical Technology Co., Ltd. lactose Shanghai MacLean Biochemical Technology Co., Ltd. Gluconic acid Shanghai MacLean Biochemical Technology Co., Ltd. Tetrasodium iminodisuccinate Shanghai MacLean Biochemical Technology Co., Ltd. Phytic Acid Shanghai Aladdin Biochemical Technology Co., Ltd. 2-Naphthalenesulfonic acid formaldehyde polymer sodium salt Shandong Lukang Pharmaceutical Co., Ltd. Sodium Methylene Bis(Methyl)naphthalene Sulfonate Shandong Lukang Pharmaceutical Co., Ltd. Acrylic acid-phosphate copolymer Shanghai MacLean Biochemical Technology Co., Ltd.
[0033] The following are specific embodiments of the present invention.
[0034] Example 1
[0035] The chromium-free passivator in this embodiment includes the following components by mass: 2 parts of zirconium nitrate; 1.5 parts of titanium sulfate; 1 part of sodium molybdate; 0.2 parts of acrylic acid-phosphate copolymer; 2.5 parts of lactose; 2 parts of chelating agent (tetrasodium iminodisuccinate); 3 parts of accelerator (phytic acid); 4 parts of dispersant (sodium salt of 2-naphthalenesulfonic acid formaldehyde polymer). The preparation method is as follows.
[0036] S1: Dissolve 2g zirconium nitrate, 1.5g titanium sulfate and 1g sodium molybdate in deionized water, and adjust the pH value to 4.0 to obtain a salt solution with a total concentration of 4.5g / L. At the same time, prepare 0.3g / L acrylic acid-phosphate copolymer solution, 2.5g / L lactose solution and 5g / L tetrasodium iminodisuccinate solution.
[0037] S2: Under stirring conditions, 3 g of phytic acid was added to 40% of the total amount of the salt solution in step S1, and the mixing temperature was maintained at 35°C.
[0038] S3: To the remaining 60% salt solution, add acrylic acid-phosphate copolymer solution, lactose solution, tetrasodium iminodisuccinate solution and the mixed solution of step S2 in sequence, stir thoroughly and adjust the pH value to 4.8, finally add 4 g of dispersant and continue stirring for 15 minutes to obtain a chromium-free passivating agent.
[0039] Example 2
[0040] The difference from Example 1 is that 2 parts of phytic acid are used, the corresponding steps are changed, and the other conditions remain unchanged.
[0041] Example 3
[0042] The difference from Example 1 is that 4 parts of phytic acid are used, the corresponding steps are changed, and the other conditions remain unchanged.
[0043] Example 4
[0044] The difference from Example 1 is that 5 parts of phytic acid are added, the corresponding steps are changed, and the other conditions remain unchanged.
[0045] Comparative Example 1
[0046] The difference from Example 1 is that phytic acid is not added, the corresponding steps are changed, and the other conditions remain unchanged.
[0047] Example 5
[0048] The chromium-free passivating agent in this embodiment includes the following components by mass: 2 parts of zirconium oxychloride; 1.5 parts of titanium nitrate; 1 part of molybdenum trioxide; 0.5 parts of acrylic acid-phosphate copolymer; 3 parts of lactose; 7 parts of chelating agent (gluconic acid); 3 parts of accelerator (phytic acid); 5 parts of dispersant (sodium methylene bismethyl naphthalene sulfonate). The preparation method is as follows.
[0049] S1: Dissolve 5g zirconium oxychloride, 1g titanium nitrate and 0.5g molybdenum trioxide in deionized water, adjust the pH value to 4.5, and obtain a salt solution with a total concentration of 6.5g / L. At the same time, prepare 0.4g / L acrylic acid-phosphate copolymer solution, 3g / L lactose solution and 7g / L gluconic acid solution.
[0050] S2: Under stirring conditions, 3 g of phytic acid was added to 50% of the total amount of the salt solution in step S1, and the mixing temperature was maintained at 38°C.
[0051] S3: To the remaining 50% salt solution, add acrylic acid-phosphate copolymer solution, lactose solution, gluconic acid solution and the mixed solution of step S2 in sequence, stir thoroughly and adjust the pH value to 5.0, finally add 5g of dispersant and continue stirring for 20 minutes to obtain a chromium-free passivating agent.
[0052] Comparative Example 2
[0053] The difference from Example 5 is that no acrylic acid-phosphate copolymer is contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0054] Comparative Example 3
[0055] The difference from Example 5 is that 0.1 part of acrylic acid-phosphate copolymer is contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0056] Comparative Example 4
[0057] The difference from Example 5 is that 0.6 parts of acrylic acid-phosphate copolymer is contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0058] Example 6
[0059] The chromium-free passivator in this embodiment includes the following components by mass: 5 parts of zirconium sulfate; 1 part of tetraisopropoxy titanium; 0.5 parts of ammonium molybdate; 0.3 parts of acrylic acid-phosphate copolymer; 2 parts of lactose; 6 parts of chelating agent (ascorbic acid); 3 parts of accelerator (phytic acid); 6 parts of dispersant (sodium salt of 2-naphthalenesulfonic acid formaldehyde polymer + sodium methylene bismethylnaphthalenesulfonate). The preparation method is as follows.
[0060] S1: Dissolve 1 g zirconium sulfate, 0.5 g tetraisopropoxytitanium and 0.5 g ammonium molybdate in deionized water, and adjust the pH value to 5.0 to obtain a salt solution with a total concentration of 2 g / L. At the same time, prepare 0.2 g / L acrylic acid-phosphate copolymer solution, 2 g / L lactose solution and 4 g / L ascorbic acid solution.
[0061] S2: Under stirring conditions, 3 g of phytic acid was added to 30% of the total amount of the salt solution in step S1, and the mixing temperature was maintained at 32°C.
[0062] S3: To the remaining 70% salt solution, acrylic acid-phosphate copolymer solution, lactose solution, ascorbic acid solution and the mixed solution of step S2 are added in sequence, and the pH value is adjusted to 4.5 after sufficient stirring. Finally, 6 g of dispersant (including 3 g each of 2-naphthalenesulfonic acid formaldehyde polymer sodium salt and methylene bismethyl naphthalene sodium sulfonate) is added and stirring is continued for 30 minutes to obtain a chromium-free passivating agent.
[0063] Comparative Example 5
[0064] The difference from Example 6 is that lactose is not contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0065] Comparative Example 6
[0066] The difference from Example 6 is that ascorbic acid is not included, the corresponding steps are changed, and the other conditions remain unchanged.
[0067] Comparative Example 7
[0068] The difference from Comparative Example 5 is that gluconic acid is used instead of ascorbic acid, the corresponding steps are changed, and the other conditions remain unchanged.
[0069] Comparative Example 8
[0070] The difference from Comparative Example 5 is that tetrasodium iminodisuccinate is used instead of ascorbic acid, the corresponding steps are changed, and the other conditions remain unchanged.
[0071] Example 7
[0072] The chromium-free passivator in this embodiment includes the following components by mass: 3 parts of zirconium nitrate; 2 parts of titanium sulfate; 1 part of sodium molybdate; 0.3 parts of acrylic acid-phosphate copolymer; 2.5 parts of lactose; 9 parts of chelating agent (ascorbic acid); 3 parts of accelerator (phytic acid); 5 parts of dispersant (sodium salt of 2-naphthalenesulfonic acid formaldehyde polymer). The preparation method is as follows.
[0073] S1: Dissolve 3g zirconium nitrate, 2g titanium sulfate and 1g sodium molybdate in deionized water, and adjust the pH value to 3.5 to obtain a salt solution with a total concentration of 6g / L. At the same time, prepare 0.3g / L acrylic acid-phosphate copolymer solution, 2.5g / L lactose solution and 9g / L tetrasodium iminodisuccinate solution.
[0074] S2: Under stirring conditions, 3 g of phytic acid was added to 35% of the total amount of the salt solution in step S1, and the mixing temperature was maintained at 37°C.
[0075] S3: To the remaining 65% salt solution, add acrylic acid-phosphate copolymer solution, lactose solution, tetrasodium iminodisuccinate solution and the mixed solution of step S2 in sequence, stir thoroughly and adjust the pH value to 5.5, finally add 5 g of dispersant and continue stirring for 25 minutes to obtain a chromium-free passivating agent.
[0076] Example 8
[0077] The difference from Example 7 is that it contains 1 part of zirconium nitrate, 1 part of titanium sulfate, and 1 part of sodium molybdate, the corresponding steps are changed, and the other conditions remain unchanged.
[0078] Example 9
[0079] The difference from Example 8 is that 3 parts of zirconium nitrate is contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0080] Example 10
[0081] The difference from Example 8 is that 2 parts of zirconium nitrate and 1 part of titanium sulfate are contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0082] Embodiment 11
[0083] The difference from Example 8 is that: 1 part of zirconium nitrate and 2 parts of sodium molybdate are contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0084] Example 12
[0085] The difference from Example 8 is that: 1 part of titanium sulfate and 2 parts of sodium molybdate are contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0086] Embodiment 13
[0087] The chromium-free passivator in this embodiment includes the following components by mass: 3 parts of zirconium nitrate; 2 parts of titanium sulfate; 1 part of sodium molybdate; 0.4 parts of acrylic acid-phosphate copolymer; 2.5 parts of lactose; 6 parts of chelating agent (ascorbic acid 3+gluconic acid 3); 3 parts of accelerator (phytic acid); 5 parts of dispersant (sodium salt of 2-naphthalenesulfonic acid formaldehyde polymer). The preparation method is as follows.
[0088] S1: 3 g zirconium nitrate, 2 g titanium sulfate and 1 g sodium molybdate were dissolved in deionized water, and the pH value was adjusted to 4.0 to obtain a salt solution with a total concentration of 6 g / L. At the same time, 0.4 g / L acrylic acid-phosphate copolymer solution, 2.5 g / L lactose solution, and chelating agent solutions of corresponding concentrations were prepared and mixed.
[0089] S2: Under stirring conditions, 3 g of phytic acid was added to 40% of the total amount of the salt solution in step S1, and the mixing temperature was maintained at 35°C.
[0090] S3: To the remaining 60% salt solution, add acrylic acid-phosphate copolymer solution, lactose solution, corresponding chelating agent solution and the mixed solution of step S2 in sequence, stir thoroughly and adjust the pH value to 4.8, finally add 4g dispersant and continue stirring for 30 minutes to obtain a chromium-free passivating agent.
[0091] Embodiment 14
[0092] The difference from Example 13 is that 6 parts of chelating agent (ascorbic acid 3+tetrasodium iminodisuccinate 3) are contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0093] Embodiment 15
[0094] The difference from Example 13 is that 6 parts of chelating agent (gluconic acid 3+tetrasodium iminodisuccinate 3) are contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0095] Example 16
[0096] The difference from Example 13 is that 6 parts of chelating agent (ascorbic acid 2+gluconic acid 2+tetrasodium iminodisuccinate 2) are contained, the corresponding steps are changed, and the other conditions remain unchanged.
[0097] Comparative Example 9
[0098] The difference from Example 13 is that the preparation method is different.
[0099] The preparation method of this comparative example is as follows.
[0100] S1: Dissolve 3g zirconium nitrate, 2g titanium sulfate and 1g sodium molybdate in deionized water, and adjust the pH value to 4.0 to obtain a salt solution with a total concentration of 6g / L. At the same time, prepare 0.4g / L acrylic acid-phosphate copolymer solution, 2.5g / L lactose solution and chelating agent solutions of corresponding concentrations.
[0101] S2: Add acrylic acid-phosphate copolymer solution, lactose solution, corresponding chelating agent solution and mixed solution of step S2 to the salt solution in sequence, stir well at 35°C, adjust pH value to 4.8, finally add 4g dispersant and 2.5g accelerator and continue stirring for 30 minutes to obtain chromium-free passivating agent.
[0102] The chromium-free passivating agent prepared in the above Examples 1 to 16 and Comparative Examples 1 to 9 is applied to copper foil for lithium batteries, and the specific operation is as follows:
[0103] Pure water (conductivity <20μs / cm, pH: 7) was used as the grooving water. The passivators prepared in the above examples and comparative examples were slowly added to the pure water, and a magnetic stirrer was used to continuously stir to ensure that the passivators were completely dissolved and evenly dispersed, so that the final concentration in the grooving solution reached 4-6%. The conductivity of the grooving solution was monitored in real time using a conductivity meter, with the goal of controlling the conductivity at 3000μs / cm. The pH value of the grooving solution was adjusted to 2.3 using an appropriate amount of dilute acid, and the grooving solution temperature was controlled to 25°C. The 10*10cm 2 The copper foil is gently placed in the bath solution and immersed in the bath to ensure that the surface of the copper foil is completely immersed in the passivation solution. The immersion time is 8 seconds, during which the copper foil can be slightly shaken to ensure that the solution is evenly in contact with the surface of the copper foil. After the immersion is completed, the copper foil is quickly removed and rinsed with deionized water to remove the residual passivation agent. Drying or other subsequent treatment steps, such as hot air drying or oven drying, can be performed as needed to obtain the corresponding chromium-free passivation agent copper foil.
[0104] The chromium-free passivation agent copper foil prepared by the above-mentioned Examples 1 to 16 and Comparative Examples 1 to 9 was subjected to relevant performance tests, and the test items were as follows:
[0105] (1) Antioxidant test
[0106] Cut three 100mmX16o samples from the left, middle and right sides of the sample width direction, and hang the samples in an air-circulating constant temperature box at (140+2)℃ with stainless steel hooks or clips. Take them out after 15 minutes and visually inspect whether there is oxidation discoloration on both sides of the copper foil.
[0107] (2) Corrosion resistance and salt spray resistance test
[0108] The salt spray test (ASTM B117) was used to evaluate the corrosion of the copper foil surface treated with different passivators in a salt spray environment to observe whether there were rust spots or corrosion products on the surface.
[0109] (3) Passivation speed test
[0110] Accurately weigh the copper foil before and after passivation, and calculate the passivation speed based on the weight change before and after passivation and the processing time. The formula is as follows:
[0111]
[0112] Where ΔW is the weight change before and after passivation (g), A is the surface area of the copper foil (cm 2 ), t is the soaking time (s).
[0113] (4) Heat resistance and stability test
[0114] The stability and heat resistance of the copper foil in a high temperature and high humidity environment were evaluated by a thermal shock test (eg, 85°C / 85% RH cycle for 7 days).
[0115] (5) Wear resistance test
[0116] The mechanical strength of the passivation film was evaluated by a wear resistance test (ASTM D4060).
[0117] The test results are recorded in Table 2 below.
[0118] Table 2 Performance test results
[0119]
[0120]
[0121] From the performance test results in Table 2, we can draw the following conclusions:
[0122] Comparison of Examples 1 to 4 and Comparative Example 1 shows that: when preparing the chromium-free passivator of the present invention, phytic acid as a promoter significantly increases the passivation speed, ensures the rapid formation of the passivation film, and exhibits the best overall performance, including oxidation resistance, corrosion resistance, stability and wear resistance. Comparative Example 1 lacking phytic acid not only leads to a significant decrease in the protective ability of the passivation film, delays the passivation process, but also has extremely poor stability of the copper foil. And when phytic acid is added in 3 parts, the comprehensive performance is the best.
[0123] Comparing Example 5 with Comparative Examples 2 to 4, it can be seen that the addition of acrylic acid-phosphate copolymer significantly improves the comprehensive performance of copper foil. The reason for this may be that the component enhances the stability and adhesion of the passivation film, making the film layer more uniform and dense. A more specific explanation may be that the acrylic acid-phosphate copolymer can bond with copper ions, and a hydroxyl group on the phosphate ester combines with hydrogen. During the drying process, the H2O generated by the combination of the hydroxyl group and hydrogen is removed, and the remaining hydroxyl groups on the phosphate ester combine with the copper ions, making the force stronger. And when the addition amount of acrylic acid-phosphate copolymer is controlled at 0.2 to 0.5 parts, the effect is best. When it is less than 0.2 parts, the stability of the film layer will be insufficient, and when it is more than 0.5 parts, it may cause other adverse reactions and affect the overall performance.
[0124] Comparison of Example 6 and Comparative Examples 5 to 8 shows that the combination of lactose and ascorbic acid not only significantly improves the antioxidant properties of the passivation film, but also greatly improves its mechanical strength and wear resistance, thereby further enhancing the stability of the metal salt in the film layer. This synergistic effect makes the passivation film outstanding in antioxidant properties, corrosion resistance and mechanical strength, ensuring the excellent protective effect and stability of the copper foil in long-term use. Analysis of the reasons may be that ascorbic acid, as a strong reducing agent, can effectively capture free radicals, interrupt the oxidation chain reaction, and reduce the oxidized metal ions to stabilize the passivation film. The multiple hydroxyl groups in the lactose molecule not only have a certain antioxidant capacity, assist ascorbic acid in scavenging free radicals, but also can fill the tiny pores in the film layer, making the film layer more dense and smooth, and enhancing the physical barrier properties and mechanical strength. In addition, lactose helps to evenly disperse ascorbic acid and other ingredients in the solution, ensuring the uniformity and consistency of the formation of the passivation film. At the same time, lactose and ascorbic acid can also form stable complexes with metal ions through their functional groups, reduce the hydrolysis and precipitation of metal ions, and further stabilize the presence of metal salts in the film layer. Finally, the two jointly adjust the pH value of the solution to maintain a suitable pH value, which is conducive to the formation and long-term stability of the passivation film.
[0125] Comparison of Examples 8 to 12 shows that the passivating agent prepared by compounding ternary metal salts can provide copper foil with better corrosion resistance and stability. Under the cooperation of these metal salts, a more compact and stable passivation film is formed on the surface of the copper foil, further improving the protective performance of the copper foil.
[0126] Combining Example 6, Comparative Examples 7-8 and Examples 13-16, it can be seen that the use of ascorbic acid alone as a chelating agent is better than compounding other chelating agents (such as gluconic acid, tetrasodium iminodisuccinate, etc.). Ascorbic acid not only has good complexing ability, but also provides additional antioxidant protection to ensure the long-term stability and durability of the passivation film. In addition, ascorbic acid can also work synergistically with lactose, making the overall performance of copper foil more excellent.
[0127] Comparison of Example 13 and Comparative Example 9 shows that: in step S2, first mixing a portion of the salt solution with the promoter can achieve effective dispersion of the promoter at a lower concentration, avoiding the influence of high concentration metal ions on the activity of the promoter. The first addition of a portion of the salt solution can provide a preliminary reaction environment for the promoter, so that the promoter can begin to play a role without being immediately interfered by other large amounts of metal ions. Adding in two batches can reduce the problem of excessive local concentration that may be caused by adding a large amount of salt solution at one time, and help to distribute all components more evenly, thereby forming a more uniform and stable passivation film. In addition, adding in batches can help slow down the occurrence of potential adverse reactions or competitive binding sites between certain components, giving more time for the various components to interact in the expected manner.
[0128] The inventors took the chromium-free passivator prepared in Example 1 as an example, and observed the electron microscope images of the copper foil before and after passivation by electron microscope scanning SEM detection. Figure 1 shown.
[0129] Depend on Figure 1 It can be seen that the surface of the copper foil treated with the chromium-free passivator is tight and has no cracks. The multifunctional groups of the chromium-free passivator of the present invention can react on the surface of the copper foil to generate strong chemical bonds. The passivation film of this composite structure can effectively improve the corrosion resistance of the copper foil and greatly improve the high temperature resistance of the copper foil without affecting the conductivity and welding performance of the copper foil itself.
[0130] The inventors took the chromium-free passivator prepared in Example 1 as an example, and prepared anti-oxidation liquids (pH 2.3) with concentrations of 4, 5, and 6%, respectively. At 140°C, the treated copper foil was immersed in the anti-oxidation liquid for 2 to 3 seconds and 6 to 8 seconds, respectively, to obtain the following: Figure 2 Photos shown.
[0131] Depend on Figure 2 It can be seen that the copper foil of the present invention has satisfactory oxidation resistance. The copper foil not treated with the passivator of the present invention has obvious color change, and the copper foil not treated with heat has slight color change after immersion, which shows that the chromium-free passivator prepared by the present invention has excellent oxidation resistance.
[0132] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A chromium-free passivating agent, characterized in that: The composition comprises the following components by weight: 1 to 15 parts of metal salt; 0.2 to 0.5 parts of acrylic acid-phosphate copolymer; 2 to 3 parts of lactose; 2 to 9 parts of chelating agent and 3 to 11 parts of auxiliary agent.
2. The chromium-free passivator according to claim 1, characterized in that: The metal salts include, by weight, 0 to 5 parts of zirconium salt, 0 to 5 parts of titanium salt and 0 to 5 parts of molybdenum salt; The metal salt includes at least one of a zirconium salt, a titanium salt or a molybdenum salt.
3. The chromium-free passivating agent according to claim 2, characterized in that: The zirconium salt is selected from one of zirconium oxychloride, zirconium nitrate or zirconium sulfate; the titanium salt is selected from one of titanium sulfate, titanium nitrate or tetraisopropoxy titanium; the molybdenum salt is selected from one of ammonium molybdate, sodium molybdate or molybdenum trioxide.
4. The chromium-free passivating agent according to claim 1, characterized in that: The chelating agent is selected from at least one of ascorbic acid, gluconic acid or tetrasodium iminodisuccinate.
5. The chromium-free passivating agent according to claim 1, characterized in that: The auxiliary agent comprises, by weight, 2 to 5 parts of an accelerator and 1 to 6 parts of a dispersant; the accelerator is phytic acid, and the dispersant is selected from sodium salt of 2-naphthalenesulfonic acid formaldehyde polymer and / or sodium methylene bismethylnaphthalene sulfonate.
6. A method for preparing the chromium-free passivating agent according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1, dissolving metal salts in deionized water respectively, adjusting the pH value, preparing corresponding salt solutions, and mixing; dissolving lactose, acrylic acid-phosphate copolymer, and chelating agent in water respectively to obtain corresponding solutions; S2, adding the accelerator to part of the salt solution in step S1 under stirring, and mixing; S3, sequentially adding the acrylic acid-phosphate copolymer solution, lactose solution, chelating agent solution and the mixed solution of step S2 to the remaining salt solution of step S1, stirring and mixing, adjusting the pH value of the solution, and finally adding a dispersant and stirring to obtain a chromium-free passivator for copper foil for lithium batteries.
7. The method for preparing a chromium-free passivating agent according to claim 6, characterized in that: In step S1, the concentration of the salt solution is 1-15 g / L, and the pH value is 3-6; the concentration of the lactose solution is 2-3 g / L; and the concentration of the acrylic acid-phosphate copolymer solution is 0.2-0.5 g / L.
8. The method for preparing a chromium-free passivating agent according to claim 6, characterized in that: In step S2, the mixing temperature is 30-40°C; the mass of the salt solution in step S2 is 30-50% of the mass of the salt solution in step S1.
9. The method for preparing a chromium-free passivating agent according to claim 6, characterized in that: In step S3, the pH value of the solution is adjusted to 4 to 5.5; after adding the dispersant, stirring is performed for 10 to 30 minutes.
10. Use of the chromium-free passivator according to any one of claims 1 to 5 in copper foil for lithium batteries.